Hearts and minds : a people's history of counterinsurgency - Gurman, Hannah (New York : New Press, The, 2013)
Since 2006, when the U.S. Army published its new field manual on counterinsurgency (the battle for ""hearts and minds""), this guiding doctrine of the U.S. military establishment continues to command broad support from liberals and conservatives alike. The first book of its kind, Hearts and Minds retells the history of counterinsurgency from the perspective of the populations whose hearts and minds have been fought over since the end of World War II. With contributions from economists, anthropologists, social historians, and journalists, the book examines key examples of cou.
5. Iraq, Part I-Counterinsurgency in Iraq by Rick Rowley6. Iraq, Part II-February 2006-December 2012: New Allies, Old Tactics by David Enders; 7. Afghanistan, Part I-"You Have to Not Mind Killing Innocents": American COIN Operations in Afghanistan and the Violence of Empire by Jeremy Kuzmarov; 8. Afghanistan, Part II-Counterinsurgency in Afghanistan: Myth or Reality? by Jean MacKenzie; Notes; About the Contributors.
Print version record.
Includes bibliographical references.
eBooks on EBSCOhost
Keywords: Counterinsurgency -- History -- 20th century -- Case studies; Counterinsurgency -- History -- 21st century -- Case studies; Counterinsurgency -- Malaysia -- History -- 20th century; Counterinsurgency -- Philippines -- History -- 20th century; Counterinsurgency -- Vietnam -- History -- 20th century; Counterinsurgency -- El Salvador -- History -- 20th century; Counterinsurgency -- Iraq -- History -- 21st century; Counterinsurgency -- Afghanistan -- History -- 21st century; Contre-rébellion -- Histoire -- 20e siècle -- Études de cas; Contre-rébellion -- Histoire -- 21e siècle -- Études de cas; Contre-rébellion -- Malaisie -- Histoire -- 20e siècle.; Contre-rébellion -- Philippines -- Histoire -- 20e siècle.; Contre-rébellion -- Viêt-nam -- Histoire -- 20e siècle.; Contre-rébellion -- Salvador -- Histoire -- 20e siècle.; Contre-rébellion -- Irak -- Histoire -- 21e siècle.; Contre-rébellion -- Afghānistān -- Histoire -- 21e siècle.; HISTORY -- Military -- Other; TECHNOLOGY & ENGINEERING -- Military Science; Counterinsurgency; Afghanistan; El Salvador; Iraq; Malaysia; Philippines; Vietnam; HISTORY / Social History; 1900-2099; Case studies; History